2020
DOI: 10.3389/fphar.2020.00489
|View full text |Cite
|
Sign up to set email alerts
|

hERG K+ Channels Promote Survival of Irradiated Leukemia Cells

Abstract: Many tumor cells express highly elevated activities of voltage-gated K + channels in the plasma membrane which are indispensable for tumor growth. To test for K + channel function during DNA damage response, we subjected human chronic myeloid leukemia (CML) cells to sub-lethal doses of ionizing radiation (0-8 Gy, 6 MV photons) and determined K + channel activity, K + channel-dependent Ca 2+ signaling, cell cycle progression, DNA repair, and clonogenic survival by whole-cell patch clamp recording, fura-2 Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…As endpoints, the percentage of cells residing in G 1 , S, and G 2 phase of cell cycle was calculated. Ionizing radiation (4 Gy) induced an increase in G 1 population and a decrease in S and G 2 population at 24 and 48 h after radiation in A172 cells (Figure 3B We have previously shown that experimental interference with electrosignaling and cell cycle control decreases the clonogenic survival of irradiated tumor cells [95,[99][100][101][102][103]. We, therefore, tested whether the observed methadone (20 µM)-mediated modulation of cell cycle control was associated with an impairment of clonogenic survival and radioresistance.…”
Section: Methadone In "Supratherapeutic" Concentrations May Modify Cell Cycle But Fails To Impair Clonogenic Survival or Radioresistance mentioning
confidence: 94%
See 3 more Smart Citations
“…As endpoints, the percentage of cells residing in G 1 , S, and G 2 phase of cell cycle was calculated. Ionizing radiation (4 Gy) induced an increase in G 1 population and a decrease in S and G 2 population at 24 and 48 h after radiation in A172 cells (Figure 3B We have previously shown that experimental interference with electrosignaling and cell cycle control decreases the clonogenic survival of irradiated tumor cells [95,[99][100][101][102][103]. We, therefore, tested whether the observed methadone (20 µM)-mediated modulation of cell cycle control was associated with an impairment of clonogenic survival and radioresistance.…”
Section: Methadone In "Supratherapeutic" Concentrations May Modify Cell Cycle But Fails To Impair Clonogenic Survival or Radioresistance mentioning
confidence: 94%
“…We, therefore, performed further in vitro experiments that addressed the effect of “supratherapeutic” and clinically relevant concentrations of methadone alone and in combination with ionizing radiation on clonogenic survival in different human glioblastoma cell lines. Since our previous work suggests that blockage of putative methadone targets may decrease clonogenic survival of irradiated tumor cells by impairment of cell cycle arrest [ 95 ], we also tested the effect of methadone and ionizing radiation on cell cycle regulation. Prior to that, we analyzed the expression of putative methadone target molecules in glioblastoma, as described in the following paragraphs.…”
Section: Evidence For a Tumoricidal Activity Of Methadonementioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have identified dysregulated potassium channel expression across many tumor types, including breast, prostate, lung, endometrium, pancreas, and others, and were extensively reviewed elsewhere [35]. In summary, the increased expression of potassium channels in cancer is associated with metastasis and tumorigenesis [38,39], higher-grade tumors [40,41], severe cancer phenotypes [42,43], cancer cell migration [44,45], proliferation through calcium regulation [46][47][48], and lower overall survival [49,50], among other effects. As such, the altered potassium ion channel expression serves central roles in neoplastic transformation and provides a toolkit that diverges from the healthy counterparts and warrants thorough investigation as a prevailing focus in cancer biology and therapeutics.…”
Section: The Role Of Ion Channels In Cancermentioning
confidence: 99%